Active Learning dalam Pembelajaran Akuntansi di SMA/SMK - Setyarini Santosa; Ika Pratiwi Simbolon; Vita Elisa Fitriana (ACADEMICS IN ACTION Journal of Community Empowerment, 2021)
Technological developments have a major impact on world businesses, such as technology-based companies. These changes also encourage for several adjustment in accounting scope. Therefore, educators are expected to be able to convey accounting knowledge in terms of its application concept in company business processes. To help delivering accounting skills, educators can use management methods in the form of active learning that focuses class activities in the active participation of each student. The purpose of this activity is for training educators to be able to apply appropriate active learning methods in accounting learning materials at SMA/SMK. When the training was conducted, each participant is invited to discuss and try to apply active learning methods. In addition, presenter also explain the data about effectiveness of active learning implementation which is shown through increasing students' understanding of the material being taught. At the end, discussions and trainings of active learning methods could provide new ideas for participants to deliver more varied subject matter.